The pretext of national strategic projects in the palm oil industry: A juridical analysis of massive deforestation and human rights violations in Papua - Nainggolan, Anggia Abraham Parlindungan (The International Journal of Politics and Sociology Research, 2026)
The designation of palm oil plantation projects as National Strategic Projects (Proyek Strategis Nasional/PSN) presents serious challenges to environmental protection due to widespread deforestation and the fulfillment of human rights, particularly in Papua, a region characterized by fragile ecosystems and Indigenous communities. This study aims to analyze the role and responsibility of the state in ensuring the protection of environmental and human rights within palm oil plantation projects classified as PSN, and to assess the alignment of palm oil business practices in Papua with the United Nations Guiding Principles on Business and Human Rights (UNGPs), specifically the principles of duty to protect, responsibility to respect, and access to remedy. Employing a normative juridical method, the research adopts a statutory approach and a conceptual approach to examine Presidential Regulation No. 60 of 2023 on the National Strategy on Business and Human Rights, relevant PSN regulations, and the UNGP framework. The findings reveal that the state has not effectively fulfilled its role in safeguarding environmental and human rights in PSN-designated palm oil projects. Rather than serving as instruments of equitable development, PSNs have marginalized Indigenous communities and imposed environmental burdens upon them without meaningful participation in decision-making processes. Moreover, palm oil business practices in Papua remain inconsistent with the UNGPs, necessitating a critical re-evaluation of PSN implementation to ensure conformity with the principles of sustainable development and social justice.